(untitled) (Journal of Pharmaceutical Negative Results, 2019)
Objective: The objective of this study was to investigate the effect of hormonal replacement therapy (HRT) in postmenopausal women onperipapillary retinal nerve fiber layer (RNFL) and macular thickness and macular volume and to compare them with postmenopausal womenwho are not on hormonal replacement therapy. Materials and Methods: The study population included postmenopausal women who are takingHRT (n = 50) and postmenopausal women who are not taking HRT (n = 50). Peripapillary retinal nerve fiber layer and macular thickness andmacular volume were evaluated using spectral domain-optical coherence tomography. Results: There was no statistically significant differencein all peripapillary RNFL thickness and macular thickness and volume parameters between the two groups, HRT and non‑HRT groups, exceptfor superior outer macular thickness and volume were significantly thicker in postmenopausal women who are taking hormonal replacementtherapy, P = 0.036 and P = 0.037, respectively. There was a positive correlation between duration on HRT with most of peripapillary RNFLand macular thickness and macular volume, but the correlation was only significant at superotemporal peripapillary RNFL. Conclusion: Ourresult does not provide strong evidence for a protective effect of postmenopausal HRT usage against ocular diseases. However, the increasedmacular thickness in superior outer macula and positively correlated peripapillary retinal nerve fiber layer at superotemporal encouraged usto think of promising positive effect of HRT on ocular structure